The Portfolio‐Driven Disposition Effect - AN, LI; ENGELBERG, JOSEPH; HENRIKSSON, MATTHEW; WANG, BAOLIAN; WILLIAMS, JARED (Journal of Finance, 2024)
ABSTRACT The disposition effect for a stock significantly weakens if the portfolio is at a gain, but is large when it is at a loss. We find this portfolio‐driven disposition effect (PDDE) in four independent settings: U.S. and Chinese archival data, as well as U.S. and Chinese experiments. The PDDE is robust to a variety of controls in regression specifications and is not explained by extreme returns, portfolio rebalancing, tax considerations, or investor heterogeneity. Our evidence suggests that investors form mental frames at both the stock and the portfolio levels and that these frames combine to generate the PDDE.